Millet in Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In semi-arid regions of Mali millet is intercropped with cowpea on 60% of cultivated plots, but production of millet, the nation's major food crop, has been in decline. Loss of fallow periods, declining soil fertility and an increasingly drier...